2018
DOI: 10.1111/jvh.12901
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hepatitis B virus infection in young Chinese blood donors born after mandatory implementation of neonatal hepatitis B vaccination nationwide

Abstract: This study was carried out to determine the incidence of hepatitis B virus (HBV) infection in the young generation born after mandatory implementation of hepatitis B vaccination since 1992. Repeat blood donors born between 1992 and 1997 were enrolled, who gave blood at least twice during the past 3 years. Donors were tested for HBV infection markers of HBsAg, anti-HBc, anti-HBs and viral DNA by immunoassays (EIAs) and nucleic acid tests (NAT). A total of 14 937 pre-donation screening qualified young repeat don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 37 publications
(90 reference statements)
1
35
0
Order By: Relevance
“…The CMR of liver cancer was significantly higher in rural residents than in urban residents (Figure 4A ), possibly because of the difference in the availability and adherence of receiving antiviral treatment [ 23 ]. The ASMR of liver cancer in the ≤39 years population continued to decrease, possibly because of HBV vaccination in newborns enforced in mainland China since 1992 [ 24 ]. Thus, the data of cancer death reflect not only the natural course of each cancer type but also the effects of public health actions.…”
Section: Discussionmentioning
confidence: 99%
“…The CMR of liver cancer was significantly higher in rural residents than in urban residents (Figure 4A ), possibly because of the difference in the availability and adherence of receiving antiviral treatment [ 23 ]. The ASMR of liver cancer in the ≤39 years population continued to decrease, possibly because of HBV vaccination in newborns enforced in mainland China since 1992 [ 24 ]. Thus, the data of cancer death reflect not only the natural course of each cancer type but also the effects of public health actions.…”
Section: Discussionmentioning
confidence: 99%
“…21 A study of 14,937 young blood donors born between 1992 and 1997 in China, that is, in the era of universal HBV vaccination program, found that 10 of 14,937 (0.067%) donors had detectable serum HBV DNA. 106 Nucleic acid amplification testing (NAT) has been established as a highly sensitive screening tool of blood donors for detection of all three viruses of HCV, HIV, and HBV and hence OBI in the most developed countries, as it is more sensitive than serological HBsAg, HCV antibody, and HIV antibody tests. 107,108 Thus, the implementation of HBV DNA detection by NAT is more sensitive than HBsAg assay as a preventive measure for HBV or OBI transmission via blood transfusion.…”
Section: Blood Products Transfusionmentioning
confidence: 99%
“…demonstrated that MP‐6 NAT with a sensitivity of 22·2 IU/ml failed to detect 50% of previous donations from Italian blood donors subsequently identified with OBI (ID‐NAT, 3·7 IU/ml) . Similarly, our recent study identified nine HBV DNA+ cases by Ultrio Plus NAT (3·4 IU/ml) in 1732 donors who previously qualified Ultrio NAT (10·4 IU/ml) . These two studies and others establish that the viral load in OBI is often very low, and in the absence of anti‐HBc testing, a very sensitive NAT assay is required to detect OBI .…”
Section: The Hbv Screening Strategy In Blood Donorsmentioning
confidence: 57%
“…Similarly, our recent study identified nine HBV DNA+ cases by Ultrio Plus NAT (3·4 IU/ml) in 1732 donors who previously qualified Ultrio NAT (10·4 IU/ml) . These two studies and others establish that the viral load in OBI is often very low, and in the absence of anti‐HBc testing, a very sensitive NAT assay is required to detect OBI . In addition, a case report involved a transmission from an ID‐NAT‐negative donation in the acute window period .…”
Section: The Hbv Screening Strategy In Blood Donorsmentioning
confidence: 84%